2000
DOI: 10.1002/(sici)1099-0690(200001)2000:1<165::aid-ejoc165>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Anion Receptors with Multiple Urea-Binding Sites

Abstract: The synthesis of macrocyclic and acyclic cleft-like anion stoichiometry (K a = 10 7 M -2 ) in DMSO, whereas Clis bound in a 1:1 stoichiometry (K a = 10 3 M -1 ). The macrocyclic receptors receptors in which four hydrogen bond donating urea moieties are present in a preorganized fashion is described. NMR form a 1:1 complex with H 2 PO 4 -(K a = 10 3 M -1 in DMSO) with a 100-fold selectivity for H 2 PO 4 over Cl -. spectroscopy shows the complex formation with H 2 PO 4 and Cl -. Cleft-like receptors bind H 2 PO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…[3] However, the design and synthesis of receptors capable of binding anionic guests is of considerable interest in the context of sensing and removal of environmental contaminants such as nitrate [4] or the radioactive pertechnate produced in the nuclear fuel cycle. [5] Synthetic receptors for anions are usually based on macrocyclic polyammonium/ guanidinium, [6,7] amides, [8,9] urea/thiourea, [10,11] and functionalized calixarenes. [12,13] The binding of anions to neutral receptors is of special significance since it avoids the competing counterion complexes present if cationic hosts are used and improves selectivity due to the dominance of directional interactions, [14] which explains the high specificity of neutral anion binding proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] However, the design and synthesis of receptors capable of binding anionic guests is of considerable interest in the context of sensing and removal of environmental contaminants such as nitrate [4] or the radioactive pertechnate produced in the nuclear fuel cycle. [5] Synthetic receptors for anions are usually based on macrocyclic polyammonium/ guanidinium, [6,7] amides, [8,9] urea/thiourea, [10,11] and functionalized calixarenes. [12,13] The binding of anions to neutral receptors is of special significance since it avoids the competing counterion complexes present if cationic hosts are used and improves selectivity due to the dominance of directional interactions, [14] which explains the high specificity of neutral anion binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we report on a study, using high level ab initio calculations, of the binding capabilities of several aro- matic rings (see Figure 1) with the bromide anion as the target, and we compare them with three molecules that have traditionally been used as binding blocks for building neutral anion receptors, namely urea, [10] thiourea [11] and squaramide, [24] each of which interacts with the anion through two hydrogen bonds. It is worth mentioning that we use two aromatic compounds that have not previously been studied as potential units for binding anions, namely 1,3,5-tricyanobenzene and 1,4,5,8,9,12-hexaazatriphenylene (HAT), and we compare them with two other aromatic rings, s-triazine and hexafluorobenzene, that have already been proposed as anion-binding units.…”
Section: Introductionmentioning
confidence: 99%
“…Our choice of introducing urea groups in the second coordination sphere of an iron‐porphyrin catalyst was motivated by their ability to bind oxygen atoms of carbonyl groups as well as carbonates . In some cases, urea groups can even capture atmospheric CO 2 as carbonates/bicarbonate .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the 1 H NMR spectral and X-ray crystal studies suggested that multiple hydrogen-bonding interactions occur between 5 and H 2 PO 4 -. tive receptors for anions based on amides have been successfully developed [16,17,[19][20][21][22][23][24] due to their neutral and hydrogen-bond acceptor properties. [24] Compared with amides, sulfonamide-based receptors for anions are rare, even though they have a strong binding ability with anions and are readily available.…”
Section: Introductionmentioning
confidence: 99%